ASSESSING THE ACCURACY OF LEARNING OBJECTIVE FORMULATION IN LESSON PLANS: A CRITICAL ANALYSIS OF INDONESIAN EFL SECONDARY SCHOOL TEACHERS - Nadya Khansa Rohimah; Joko Nurkamto; Kristian Adi Putra (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
The formulation of specific and achievable learning outcomes remains critical in the approach to teaching, especially in the EFL context. At the same time, some of the challenges mentioned by educators indicate the problem of defining the objectives, goals and outcomes of a curriculum. This research aims to critically analyze how Indonesian EFL secondary school teachers construct learning objectives in the context of Kurikulum 2013 and Kurikulum Merdeka. This study was an exploratory study using qualitative descriptive research methods. The inclusion of two teachers from the same school was intentional to reduce external bias. Triangulated qualitative data sources included participants' written consent forms and principal interviews, and quantitative lesson plan documents were evaluated using the ABCD and SMART model checklists. Strengths identified centered on high-level thinking skills and child-centered processes, while weaknesses included many frameworks and a lack of objective criteria. Based on the study's findings, a combination of detailed instructional contexts and performance bench marking can positively enhance the formulation of learning goals. They advance knowledge about approaches to implementing and refining instructional practices and goals in conjunction with curricular expectations in different contexts.